KEHADIRAN GELOMBANG SOLITER DAN TRANSPOR SESAAT SEDIMEN TERSUSPENSI DI PERAIRAN PANTAI BENGKULU TENGAH - Kusmanto, Edi; Hasanudin, Muhammad (OLDI (Oseanologi dan Limnologi di Indonesia), 2019)
Existence of Solitary Waves and Transient Suspended Sediment Transport in the Coastal Waters of Central Bengkulu. Coastal abrasion and suspended sediment transport driven by waves is occurring dreadfully in the coastal waters of Central Bengkulu. The abrasion tends to be accelerated by solitary waves during the southeast monsoon season. The primary data were obtained  on 17-26 July 2014, while the secondary data derived from Google Maps imageries obtained on 17 June 2014, representing the southeast monsoon season. The primary data were collected by 1200 KHz Acoustic Doppler Current Profiler (ADCP) for water currents, a single beam Echosounder for  depths, Garmin 276C GPS receiver for coordinate positions, RBR-TWR2050 (installed at at a fixed point at 102.2219 °E and 3.6916 °S and depth of 9 m) for height and wave periods, and a compass for the direction of wave propagation. The secondary data included Astrium satellite imageries compiled by Google Earth and displayed as Google Maps images on 17 June 2014. These images were used for identifying the appearance of wave groups and by using a feature in Google Earth, it showed that the estimated distance between wave packets hitting the coast accounted for 147 m. This study showed the existence of solitary waves with height and wave period of 1.02 m and 13.85 seconds respectively, while the wave length reached 147.7 m. The wave energy and wave energy flux were 1123.12 Jm-2 and 12018.94 Jm-1s-1, calculated by using the cnoidal wave theory and solved by the KdV equation. These solitary waves have large destructive forces on unstable cliffs along the coasts. Derived from coastal abrasion processes and shown by the ADCP backscatter intensity with the highest of 146 dB, the suspended sediments were likely to be transported by water currents with an average speed of 25.99 cm s-1 in the dominant direction to the south - southeast; and the sediments were deposited along the coast of Bengkulu City.